Metal modified adsorbent as well as preparation method and application thereof in circulating hydrogen purification
By introducing metal modified adsorbents that contain copper -containing components such as copper -containing components on the adsorbing carrier, the problem of high energy consumption and phosphorus hydroxide in circulating hydrogen purification is difficult to remove, and high -efficiency and low energy consumption hydrogen purification effects are achieved.
Patent Information
- Application Number
- CN202411467826.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
AI Technical Summary
In the purification process of circulating hydrogen in polycrystalline silicon production, the prior art has problems such as high energy consumption, high cost and phosphorus impurity poisoning, making it difficult to effectively remove low boiling point phosphide.
Using metal modified adsorbent, the adsorbent is loaded with copper -containing activity components, additive metal components, oxidant auxiliary components and ionic liquids on the absorbing carrier. Has high adsorption-oxidation efficiency.
The efficient adsorption and stability of phosphor hydroxide is realized, the operation is simple and the energy consumption is low. It is suitable for cyclic hydrogen purification in polysilicon production, and the adsorption rate can reach more than 95%.
Smart Images

Figure CN119327420A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polysilicon production, and in particular to a metal-modified adsorbent and a preparation method thereof and application thereof in circulating hydrogen purification. Background Art
[0002] Polysilicon is a basic material widely used in the photovoltaic and semiconductor industries. The purity of polysilicon will significantly affect the performance of semiconductor devices. For photovoltaic materials, impurities in polysilicon affect the electrical properties of the material, such as conductivity, carrier lifetime, PN junction withstand voltage and threshold voltage. The current photovoltaic market is accelerating the transition from P-type cells to N-type cells, and the demand for N-type polysilicon is rising rapidly. Compared with the solar-grade technical indicators of P-type polysilicon, N-type polysilicon has more stringent quality requirements, which not only requires the silicon material to be dense and stable in quality, but also limits the content of various impurities (donors, acceptors, metals, etc.) to a lower level.
[0003] In the production of high-purity polysilicon, the purity of raw materials is one of the key factors. The third-generation polysilicon production process has achieved a completely closed-loop production. A large amount of reducing tail gas such as H2, SiHCl3 and HCl needs to be recovered, purified and reused, among which P is the main donor impurity. In the hydrogen recovery link, impurities with higher boiling points such as PCl3, PCl5 and PHCl2 can be removed by pressurized condensation, chlorosilane leaching and absorption, etc., but low-boiling point phosphine represented by PH3 is difficult to be removed by conventional activated carbon adsorbents due to the limitation of adsorption equilibrium. It will also accumulate with the continuous circulation of H2 in the reduction part, and ultimately affect the purity of polysilicon.
[0004] In the prior art, for the purification of recovered hydrogen, patent CN105293438B discloses a multi-stage cooling + adsorption process, in which the first stage of cooling cools H2 to 0-30°C and removes boron-containing impurities through an activated carbon adsorption column; the second stage of cooling deeply cools H2 to between -88°C and -68°C and removes phosphorus-containing impurities through a silica gel adsorption column. Patent CN117263141A discloses a method for purifying circulating hydrogen in polysilicon production, in which a chlorine supply agent is added to the tail gas condensate to convert most of the boron and phosphorus hydrogen compounds into boron and phosphorus chlorides with higher boiling points, and then removes them by distillation. Patent CN113233420A proposes a two-stage purification method of activated carbon adsorption and CVD pretreatment system. The pretreatment system uses a molecular sieve loaded Fe-Ni-Co ternary amorphous alloy as a catalyst to oxidize phosphorus hydrogen compounds to phosphorus or metal phosphonium compounds at 200-250°C for removal. Patent CN102328906B uses two sets of metal palladium composite membrane hydrogen purifiers connected in series to purify the trichlorosilane reduction circulating hydrogen. The purified ultra-pure and high-purity hydrogen can be used as raw gas for the reduction and cold hydrogenation sections respectively.
[0005] However, the technical solutions disclosed in the above patents also have shortcomings. For example, the deep-cold adsorption process and the catalytic conversion before CVD require a strict low-temperature or high-temperature environment, which consumes a lot of energy. The purification of hydrogen by metal palladium membrane also requires a high-temperature environment, which consumes a lot of energy. In addition, there are the problems of high cost of using precious metal palladium and palladium membrane poisoning caused by phosphorus impurities. The method of adding a chlorine supply agent for chlorination conversion has the risk of introducing new impurities. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a metal-modified adsorbent and a preparation method thereof and application thereof in circulating hydrogen purification.
[0007] In order to achieve the above object, the present invention provides a metal-modified adsorbent, which comprises an adsorption carrier and a copper-containing active component, an auxiliary metal component and an oxidizing auxiliary component loaded on the adsorption carrier, wherein the adsorption carrier is also loaded with an ionic liquid; the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 the following.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned metal-modified adsorbent, the method comprising the following steps:
[0009] (1) preparing a first metal salt solution including a copper-containing active component, an auxiliary metal component, a dispersant and an ionic liquid;
[0010] (2) adding an oxidizing agent component to the first metal salt solution to obtain a second metal salt solution;
[0011] (3) contacting the second metal salt solution with an adsorption carrier so that the copper-containing active component, the auxiliary metal component, the oxidation auxiliary component and the ionic liquid are loaded on the adsorption carrier to obtain a metal-modified precursor;
[0012] (4) drying the metal-modified precursor to obtain the metal-modified adsorbent;
[0013] The method enables the obtained metal-modified adsorbent to satisfy the following conditions: the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 the following.
[0014] A third aspect of the present invention provides a use of the above-mentioned metal-modified adsorbent in the purification of circulating hydrogen.
[0015] The present invention introduces a copper-containing active component, an auxiliary metal component, an oxidation auxiliary component and an ionic liquid on an adsorption carrier to obtain a metal-modified adsorbent. The number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 It has abundant surface active sites, the metal species on the surface are highly stable and not easy to lose, and has excellent adsorption performance and service life. Especially when used in the circulating hydrogen purification process in polysilicon production, it can have extremely high adsorption-oxidation efficiency for phosphine hydride, and is simple to operate and has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a transmission electron micrograph of the metal-modified adsorbent sample prepared in Example 1;
[0017] Figure 2 This is a transmission electron microscopy image of the metal-modified adsorbent sample prepared in Comparative Example 3.
[0018] Figure 1 and Figure 2 The black spots are the metal copper and zinc species loaded on the surface of activated carbon. Figure 1 It can be seen that the metal species on the surface of the metal-modified adsorbent prepared in Example 1 are very uniformly distributed, and almost no large agglomerates are seen. The number of metal agglomerates with a size of more than 20 nm is 0.2×10 6 Pieces / mm 2 ;Depend on Figure 2 It can be seen that the metal modified adsorbent prepared in Comparative Example 3 has serious agglomeration of metal species on the surface, and obvious black particles can be seen. The number of metal agglomerates with a size of more than 20 nm is 9.6×10 6 Pieces / mm 2 , much higher than Example 1. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] In one aspect, the present invention provides a metal-modified adsorbent, which comprises an adsorption carrier and a copper-containing active component, an auxiliary metal component and an oxidizing auxiliary component loaded on the adsorption carrier, wherein the adsorption carrier is further loaded with an ionic liquid; the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 the following.
[0021] According to the present invention, by introducing a copper-containing active component, an auxiliary metal component, an oxidation auxiliary component and an ionic liquid on the adsorption carrier, the synergistic effect between the components can be utilized to greatly improve the adsorption performance of the metal-modified adsorbent, especially the adsorption activity and stability of phosphine. Through the interaction between the above components, each component can have excellent dispersibility on the surface of the metal-modified adsorbent, so the degree of metal agglomeration on the adsorbent can also be controlled at a low level. In order to further improve the performance of the metal-modified adsorbent, preferably, the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2×10 6 Pieces / mm 2 Below, preferably 1.5×10 6 Pieces / mm 2 Below, more preferably 1.2×10 6 Pieces / mm 2 Below, more preferably 0.2×10 6 -0.8×10 6 Pieces / mm 2 , for example, it can be 0.2×10 6 Pieces / mm 2 , 0.4×10 6 Pieces / mm 2 , 0.7×10 6 Pieces / mm 2 and 0.8×10 6 Pieces / mm 2 The range between the values and any values in between.
[0022] According to the present invention, the components in the metal-modified adsorbent are evenly distributed, especially the metal components have better dispersibility, and the content of large-sized metal agglomerates is lower. Preferably, in the metal-modified adsorbent, the distribution of metal component particles shows that the content of metal agglomerates with a particle size below 15nm accounts for more than 70wt%, more preferably more than 80wt%, for example, 85-95wt%. The existing metal-modified adsorbent has agglomerates of higher sizes of metal components, and the content of metal agglomerates with a particle size of more than 30nm accounts for more than 80wt%, even more than 90wt%, especially more than 95wt%. Therefore, the metal-modified adsorbent of the present invention can show more excellent adsorption, especially in the adsorption purification of circulating hydrogen in polysilicon production, a higher adsorption rate for phosphine can be obtained.
[0023] According to the present invention, in order to improve the performance of the metal-modified adsorbent, preferably, the loading amount of copper element in the metal-modified adsorbent is 1-15wt%, preferably 5-10wt%, for example, it can be 5wt%, 6.1wt%, 8wt% and 10wt% and any value range therebetween.
[0024] According to the present invention, in order to enhance the synergistic effect between the components, thereby further increasing the surface active sites of the metal-modified adsorbent and improving the stability of the metal species on its surface, preferably, the ratio of the molar amount of the copper-containing active component to the molar amount of the auxiliary metal component is 1:0.01-2, preferably 1:0.05-1, for example, it can be 1:0.05, 1:0.2, 1:0.5, 1:0.8 and 1:1 and the range between any values thereof. Preferably, the ratio of the total molar amount of the copper-containing active component and the auxiliary metal component, the molar amount of the oxidation auxiliary component and the molar amount of the ionic liquid is 1:0.05-0.5:0.1-2, preferably 1:0.1-0.3:0.3-1.5, for example, it can be 1:0.2:1, 1:0.1:0.8, 1:0.3:0.3, 1:0.1:1.5 and 1:0.2:1.2 and the range between any values thereof.
[0025] According to the present invention, the adsorption carrier can be selected in a wide range. In order to enhance the affinity between the adsorption carrier and the metal species and facilitate the introduction of each component, preferably, the adsorption carrier is selected from one or more of activated carbon, molecular sieves, activated alumina, silica gel, titanium dioxide and ceramics, preferably one or more of coconut shell activated carbon, fruit shell activated carbon, wood activated carbon, coal-based activated carbon, resin-based activated carbon and rubber activated carbon, more preferably one or more of coconut shell activated carbon, fruit shell activated carbon and wood activated carbon.
[0026] According to the present invention, the copper-containing active component, as a key metal active component, can be selected in a wide range. In order to better improve the adsorption activity and adsorption efficiency of the metal-modified adsorbent, preferably, the copper-containing active component is selected from one or more of copper halides, sulfates, nitrates and acetates (for example, copper chloride, copper bromide, copper sulfate, copper nitrate and copper acetate, etc.), preferably one or more of copper halides, more preferably one or more of copper chlorides, and further preferably copper chloride and / or cuprous chloride.
[0027] According to the present invention, the auxiliary metal component can be matched with the copper-containing active component to obtain better surface metal species and cooperate with other components, thereby enhancing the stability of the metal-modified adsorbent and further improving the adsorption performance. The auxiliary metal component can be selected in a wide range. In order to better cooperate with the copper-containing active component and other components, preferably, the auxiliary metal component is selected from one or more of the halides, sulfates, nitrates and acetates of iron, silver, zinc, cerium, cobalt and nickel (for example, it can be ferric chloride, silver sulfate, cobalt sulfate, silver nitrate and nickel acetate, etc.), preferably one or more of the halides of iron, silver, zinc, cerium, cobalt and nickel, more preferably one or more of the chlorides of iron, silver, zinc, cerium, cobalt and nickel, and further preferably one or more of ferric chloride, silver chloride, zinc chloride, cerium chloride, cobalt chloride and nickel chloride.
[0028] According to the present invention, under the coordinated action of the oxidation aid component and other components, the reduction behavior of the active metal on the surface of the adsorption carrier can be significantly inhibited, and the content of the oxidized active metal can be greatly increased, thereby improving the adsorption stability of the metal-modified adsorbent and the adsorption performance of the reduced phosphine. The oxidation aid can be selected in a wide range. In order to further improve and extend the adsorption life and adsorption performance of the metal-modified adsorbent, preferably, the oxidation aid component is selected from one or more of cerium salts, molybdenum salts and manganese salts (for example, ammonium cerium nitrate, ammonium molybdate, cerium sulfate, potassium permanganate and sodium permanganate, etc.), preferably one or more of cerium salts, more preferably ammonium cerium nitrate and / or cerium sulfate.
[0029] According to the present invention, the ionic liquid can not only be used as an excellent dispersed phase to optimize the dispersibility of metal species and other components on the surface of the adsorption carrier, but also can be used as a coordinating group to enhance the interaction and affinity between the metal species and the adsorption carrier by means of the strong coordination between the negative ions and the metal species, thereby inhibiting the loss of metal species during the gas adsorption process and greatly improving the stability of the metal-modified adsorbent. The ionic liquid can be selected in a wide range. In order to obtain a metal-modified adsorbent with better performance, preferably, the cation in the ionic liquid is selected from one or more of imidazole cations, pyridinium cations, quaternary ammonium salt cations, quaternary phosphonium salt cations and morpholine cations, and the anion is selected from BF4 - PF6 - 、F - , Cl - Br - and I - More preferably, the cation in the ionic liquid is selected from one or more of imidazole cations and quaternary ammonium salt cations, and the anion is selected from Cl - Br - and I - The ionic liquid may be selected from one or more of 1-butyl-3-methylimidazolium chloride ionic liquid, 1-ethyl-3-methylimidazolium chloride ionic liquid, tetrabutylammonium chloride ionic liquid and tetrabutylammonium bromide ionic liquid.
[0030] The second aspect of the present invention provides a method for preparing the above-mentioned metal-modified adsorbent, the method comprising the following steps:
[0031] (1) preparing a first metal salt solution including a copper-containing active component, an auxiliary metal component, a dispersant and an ionic liquid;
[0032] (2) adding an oxidizing agent component to the first metal salt solution to obtain a second metal salt solution;
[0033] (3) contacting the second metal salt solution with an adsorption carrier so that the copper-containing active component, the auxiliary metal component, the oxidation auxiliary component and the ionic liquid are loaded on the adsorption carrier to obtain a metal-modified precursor;
[0034] (4) drying the metal-modified precursor to obtain the metal-modified adsorbent;
[0035] The method enables the obtained metal-modified adsorbent to satisfy the following conditions: the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 the following.
[0036] According to the present invention, the metal agglomeration degree of the metal modified adsorbent prepared by the above method can be controlled at a relatively low level. Preferably, the above method enables the obtained metal modified adsorbent to satisfy: the number of metal agglomerates with a size of more than 20 nm on the metal modified adsorbent is 2×10 6 Pieces / mm 2 Below, preferably 1.5×10 6 Pieces / mm 2 Below, more preferably 1.2×10 6 Pieces / mm 2 Below, more preferably 0.2×10 6 -0.8×10 6 Pieces / mm 2 , for example, it can be 0.2×10 6 Pieces / mm 2 , 0.4×10 6 Pieces / mm 2 , 0.7×10 6 Pieces / mm 2 and 0.8×10 6 Pieces / mm 2 The range between the values and any values in between.
[0037] The loading amount of the copper element in the metal-modified adsorbent of the second aspect of the present invention can be selected and optimized from the loading amounts of the copper element described above, and the present invention will not be described in detail here.
[0038] The adsorption carrier, copper-containing active component, auxiliary metal component, oxidizing auxiliary component and ionic liquid of the second aspect of the present invention can be selected and preferred from the adsorption carrier, copper-containing active component, auxiliary metal component, oxidizing auxiliary component and ionic liquid described above, and the present invention will not repeat them here. Among them, the amount of the adsorption carrier can be adjusted within a wide range. Preferably, the amount of the adsorption carrier is such that the copper element loading in the obtained metal-modified adsorbent is 1-15wt%, preferably 5-10wt%.
[0039] According to the present invention, in step (1) of the above method, in order to obtain a first metal salt solution with good properties and further obtain a metal-modified adsorbent with better performance, preferably, relative to 1 mol of the copper-containing active component, the amount of the auxiliary metal component is 0.01-2 mol, preferably 0.05-1 mol, for example, it can be 0.05 mol, 0.1 mol, 0.5 mol and 1 mol and the range between any values thereof. Preferably, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component, the amount of the ionic liquid is 0.1-2 mol, preferably 0.3-1.5 mol, for example, it can be 0.3 mol, 0.8 mol, 1 mol and 1.5 mol and the range between any values thereof. Preferably, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component, the amount of the dispersant is 0.001-0.1 mol, preferably 0.005-0.05 mol, for example, it can be 0.005 mol, 0.01 mol, 0.03 mol and 0.05 mol and the range between any values thereof. Preferably, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component, the amount of the solvent of the first metal salt solution is 15-500 mL, preferably 35-350 mL, for example, it can be 50 mL, 100 mL, 250 mL and 300 mL and the range between any values thereof.
[0040] According to the present invention, in step (1) of the above method, the dispersant can well improve the dispersibility of each component during the preparation process, and further can make each component have good dispersibility in the prepared metal-modified adsorbent, so that the surface active sites of the metal-modified adsorbent are more abundant and the adsorption effect is better. The dispersant can be selected in a wide range. In order to further improve the compatibility of each component and optimize the dispersibility of each component, preferably, the dispersant is selected from one or more of ethylene glycol, glycerol, tannic acid, polyethylene glycol, polyacrylamide and polyvinyl pyrrolidone, preferably one or more of ethylene glycol, glycerol and polyvinyl pyrrolidone.
[0041] According to the present invention, in step (1) of the above method, the solvent of the first metal salt solution can be selected from a wide range. In order to fully contact the components and obtain a better first metal salt solution, preferably, the solvent is selected from one or more of water, methanol, ethanol, propylene glycol, acetonitrile, acetone, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone, preferably one or more of water, methanol, ethanol, acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone. More preferably, the solvent of the first metal salt solution is a mixed solvent of water and N,N-dimethylformamide (the mass ratio of water to N,N-dimethylformamide is 1:0.1-2, preferably 1:0.2-1, for example, it can be 1:0.2:1:0.5, 1:0.8 and 1:1 and any range between these values).
[0042] According to the present invention, the specific preparation process of step (1) of the above method may include the following operations: dissolving the copper-containing active component, the auxiliary metal component and the dispersant in a solvent, adding an ionic liquid for reaction, and obtaining a first metal salt solution. Preferably, the reaction conditions are a temperature of 0-90°C and a time of 3-24h; preferably a temperature of 20-70°C (for example, it may be a range of values such as 20°C, 40°C, 50°C and 70°C and any values thereof), and a time of 3-16h (for example, it may be a range of values such as 3h, 5h, 10h, 12h and 16h and any values thereof).
[0043] According to the present invention, in step (2) of the above method, in order to obtain a second metal salt solution with better properties, preferably, the oxidation aid component is provided in the form of a solution, and the solvent for dissolving the oxidation aid component is selected from one or more of water, methanol, ethanol, propylene glycol, acetonitrile, acetone, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone, preferably one or more of water, methanol, ethanol, acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone. Preferably, relative to 1 mol of the oxidation aid component, the amount of the solvent for dissolving the oxidation aid component is 15-500 mL, preferably 35-350 mL, for example, it can be 35 mL, 120 mL, 230 mL and 350 mL and the range between any values thereof. Preferably, when the oxidation aid component is provided in the form of a solution, the solution is acidic; more preferably, the pH of the solution of the oxidation aid component is 5.5-6.5, for example, 5.5, 6, 6.2 and 6.5 and any range between them. Preferably, relative to 1 mol of the total amount of the copper-containing active component and the aid metal component, the amount of the oxidation aid component is 0.05-0.5 mol, preferably 0.1-0.3 mol, for example, 0.1 mol, 0.15 mol, 0.25 mol and 0.3 mol and any range between them.
[0044] According to the present invention, the specific preparation process of step (2) of the above method may include, for example, the following operations: dissolving the oxidation aid component in a solvent and adjusting the acidity with an acid solution to obtain a solution of the oxidation aid component, and then adding the solution of the oxidation aid component to a first metal salt solution to obtain a second metal salt solution. The acid solution may be, for example, one or more aqueous solutions of hydrochloric acid, sulfuric acid, nitric acid and acetic acid with a concentration of 0.5-5 mol / L.
[0045] According to the present invention, in step (3) of the above method, the second metal salt solution can be contacted with the adsorption carrier in a manner that adopts a variety of methods used in the art to load metal components and the like on a carrier, such as impregnation and / or spraying, wherein the equal volume impregnation method is preferably adopted.
[0046] According to the present invention, in step (4) of the above method, in order to obtain a metal-modified adsorbent with better performance, preferably, the drying treatment includes subjecting the metal-modified precursor to a first drying treatment and a second drying treatment. Preferably, the conditions of the first drying treatment include: a temperature of 60-90°C, a time of 2-36h, and a heating rate of 0.1-3°C / min; preferably, a temperature of 70-80°C (for example, it can be a range between values such as 70°C, 72°C, 75°C, 78°C and 80°C, and any values thereof), a time of 6-12h (for example, it can be a range between values such as 6h, 8h, 10h and 12h, and any values thereof), and a heating rate of 0.5-2°C / min (for example, it can be a range between values such as 0.5°C / min, 1°C / min, 1.6°C / min and 2°C / min, and any values thereof). Preferably, the conditions of the second drying treatment include: temperature 100-180°C, time 4-16h, heating rate 4-8°C / min; preferably temperature 120-160°C (for example, it can be 120°C, 135°C, 140°C, 150°C and 160°C and the range between any values thereof), time 6-12h (for example, it can be 6h, 8h, 10h and 12h and the range between any values thereof), heating rate 5-7°C / min (for example, it can be 5°C / min, 5.5°C / min, 6°C / min and 7°C / min and the range between any values thereof). The starting temperature of the first drying treatment can usually be 20-40°C, and it can also be appropriately beyond this range. The starting temperature of the second drying treatment is the drying temperature of the first drying treatment. Preferably, the first drying treatment and the second drying treatment are carried out under an inactive gas atmosphere. Preferably, the inactive gas is selected from nitrogen and / or argon.
[0047] A third aspect of the present invention provides a use of the above-mentioned metal-modified adsorbent in the purification of circulating hydrogen.
[0048] The present invention introduces a copper-containing active component, an auxiliary metal component, an oxidation auxiliary component and an ionic liquid on an adsorption carrier to obtain a metal-modified adsorbent. The number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 It has excellent adsorption performance and stability, especially when used in the circulating hydrogen purification process in polysilicon production. Not only can the adsorption rate of phosphine be as high as 95% or more, it also has excellent stability and service life, and is easy to operate and has low energy consumption.
[0049] The present invention will be described in detail below through examples.
[0050] In the following examples, the devices used are all conventional experimental devices in this field, the experimental operations adopted are all conventional operations in this field, and the raw materials, reagents, etc. used can be obtained commercially. Among them, the parameters of coconut shell activated carbon are: iodine value 1000, carbon tetrachloride adsorption value 60%, strength ≥98%, ash content ≤2wt%, moisture ≤5wt%, bulk density 0.5-0.55g / cm 3 The appearance is granular. Polyvinyl pyrrolidone was purchased from Sigma-Aldrich, with the brand name K15 (molecular weight 5500).
[0051] Example 1
[0052] (1) Copper chloride, zinc chloride and glycerol (0.5 mol of zinc chloride relative to 1 mol of copper chloride; 0.05 mol of glycerol relative to 1 mol of the total amount of copper chloride and zinc chloride) are dissolved in a mixed solvent of water and N,N-dimethylformamide (the mass ratio of water to N,N-dimethylformamide is 1:0.5; the amount of the mixed solvent relative to 1 mol of the total amount of copper chloride and zinc chloride is 300 mL), 1-butyl-3-methylimidazolium chloride ionic liquid is added (1 mol of 1-butyl-3-methylimidazolium chloride ionic liquid relative to 1 mol of the total amount of copper chloride and zinc chloride) and reacted at 50° C. for 3 h to obtain a first metal salt solution.
[0053] (2) Dissolve ammonium cerium nitrate (0.15 mol relative to 1 mol of the total amount of copper chloride and zinc chloride) in water (200 mL relative to 1 mol of ammonium cerium nitrate) and adjust the pH to 6 with a 2 mol / L nitric acid aqueous solution to obtain an ammonium cerium nitrate aqueous solution. Add the ammonium cerium nitrate aqueous solution to the first metal salt solution, mix well, and obtain a second metal salt solution.
[0054] (3) The second metal salt solution is uniformly loaded onto the coconut shell activated carbon by equal volume impregnation to obtain a metal-modified precursor.
[0055] (4) After the metal-modified precursor is dried, the temperature is raised from room temperature to 80°C at a heating rate of 0.5°C / min in a nitrogen atmosphere, and dried at 80°C for 6 hours. Then, the temperature is raised from 80°C to 150°C at a heating rate of 5°C / min, and dried at 150°C for 12 hours. After drying, the system is naturally cooled to room temperature to obtain the metal-modified adsorbent MA-1. The copper loading in the metal-modified adsorbent MA-1 is about 6.1wt%.
[0056] like Figure 1 As shown in Figure 2, the number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-1 can be measured by transmission electron microscopy to be 0.2×10 6 Pieces / mm2 ; And in the obtained metal-modified adsorbent, the distribution of metal component particles shows that the content of metal agglomerates with a particle size below 15nm accounts for about 90wt%.
[0057] Example 2
[0058] (1) Cuprous chloride, cobalt chloride and glycerol (the amount of cobalt chloride is 0.8 mol relative to 1 mol of cuprous chloride; the amount of glycerol is 0.03 mol relative to the total amount of cuprous chloride and cobalt chloride) are dissolved in 1,3-dimethylimidazolidinone (the amount of 1,3-dimethylimidazolidinone is 350 mL relative to the total amount of cuprous chloride and cobalt chloride) and tetrabutylammonium chloride ionic liquid is added (the amount of tetrabutylammonium chloride ionic liquid is 1.5 mol relative to the total amount of cuprous chloride and cobalt chloride) and reacted at 30° C. for 3 h to obtain a first metal salt solution.
[0059] (2) Dissolve ammonium cerium nitrate (0.15 mol relative to the total amount of 1 mol of cuprous chloride and cobalt chloride) in water (200 mL relative to 1 mol of ammonium cerium nitrate) and adjust the pH to 5.5 with a 2 mol / L hydrochloric acid aqueous solution to obtain an ammonium cerium nitrate aqueous solution. Add the ammonium cerium nitrate aqueous solution to the first metal salt solution, mix well, and obtain a second metal salt solution.
[0060] (3) The second metal salt solution is uniformly loaded onto the coconut shell activated carbon by equal volume impregnation to obtain a metal-modified precursor.
[0061] (4) After the metal-modified precursor is dried, the temperature is raised from room temperature to 75°C at a heating rate of 1°C / min in a nitrogen atmosphere, and dried at 75°C for 10 hours. Then, the temperature is raised from 75°C to 130°C at a heating rate of 6°C / min, and dried at 130°C for 8 hours. After drying, the system is naturally cooled to room temperature to obtain the metal-modified adsorbent MA-2. The copper loading in the metal-modified adsorbent MA-1 is about 6.35wt%.
[0062] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-2 was 0.6×10 6 Pieces / mm 2 .
[0063] Example 3
[0064] (1) Copper chloride, silver chloride and ethylene glycol (the amount of silver chloride is 0.05 mol relative to 1 mol of copper chloride; the amount of ethylene glycol is 0.01 mol relative to the total amount of copper chloride and silver chloride) are dissolved in methanol (the amount of methanol is 300 mL relative to the total amount of copper chloride and silver chloride), and 1-ethyl-3-methylimidazolium chloride ionic liquid is added (the amount of 1-ethyl-3-methylimidazolium chloride ionic liquid is 1 mol relative to the total amount of copper chloride and silver chloride) and reacted at 70° C. for 8 h to obtain a first metal salt solution.
[0065] (2) Dissolve cerium sulfate (0.15 mol relative to the total amount of 1 mol of copper chloride and silver chloride) in methanol (250 mL relative to 1 mol of cerium sulfate) and adjust the pH to 6.5 with a 2 mol / L sulfuric acid aqueous solution to obtain a cerium sulfate aqueous solution. Add the cerium sulfate aqueous solution to the first metal salt solution and mix well to obtain a second metal salt solution.
[0066] (3) The second metal salt solution is uniformly loaded onto the coconut shell activated carbon by equal volume impregnation to obtain a metal-modified precursor.
[0067] (4) After the metal-modified precursor is dried, the temperature is raised from room temperature to 80°C at a heating rate of 2°C / min in a nitrogen atmosphere, and dried at 80°C for 10 hours. Then, the temperature is raised from 80°C to 160°C at a heating rate of 7°C / min, and dried at 160°C for 10 hours. After drying, the system is naturally cooled to room temperature to obtain the metal-modified adsorbent MA-3. The copper loading in the metal-modified adsorbent MA-1 is about 10wt%.
[0068] The number of metal aggregates with a size of more than 20 nm on the metal modified adsorbent MA-3 was 0.5×10 6 Pieces / mm 2 .
[0069] Example 4
[0070] The method of Example 1 is different in that in step (1), the amount of zinc chloride used is 0.01 mol relative to 1 mol of copper chloride, and the metal-modified adsorbent MA-4 is finally prepared.
[0071] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-4 was 1.5×10 6 Pieces / mm 2 .
[0072] Example 5
[0073] The method of Example 1 is different in that in step (1), the amount of zinc chloride used is 1.5 mol relative to 1 mol of copper chloride, and the metal-modified adsorbent MA-5 is finally prepared.
[0074] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-5 was 1.4×10 6 Pieces / mm 2 .
[0075] Example 6
[0076] The method of Example 1 is different in that in step (1), the amount of 1-butyl-3-methylimidazolium chloride ionic liquid used is 0.2 mol relative to the total amount of 1 mol of copper chloride and zinc chloride, and finally a metal-modified adsorbent MA-6 is prepared.
[0077] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-6 was 1.8×10 6 Pieces / mm 2 .
[0078] Example 7
[0079] The method of Example 1 is different in that in step (1), the amount of 1-butyl-3-methylimidazolium chloride ionic liquid used is 2 mol relative to 1 mol of the total amount of copper chloride and zinc chloride, and finally a metal-modified adsorbent MA-7 is prepared.
[0080] The number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent MA-7 was 1.3×10 6 Pieces / mm 2 .
[0081] Example 8
[0082] The method of Example 1 is different in that in step (2), the amount of ammonium cerium nitrate used is 0.05 mol relative to the total amount of 1 mol of copper chloride and zinc chloride, and finally the metal modified adsorbent MA-8 is prepared.
[0083] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-8 was 1.3×10 6 Pieces / mm 2 .
[0084] Example 9
[0085] The method of Example 1 is different in that in step (2), the amount of ammonium cerium nitrate used is 0.5 mol relative to 1 mol of the total amount of copper chloride and zinc chloride, and finally a metal-modified adsorbent MA-9 is prepared.
[0086] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-9 was 1.2×10 6 Pieces / mm 2 .
[0087] Example 10
[0088] The method of Example 1 is different in that in step (1), copper chloride is replaced by copper sulfate, and finally the metal-modified adsorbent MA-10 is prepared.
[0089] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-10 was 1.1×10 6 Pieces / mm 2 .
[0090] Embodiment 11
[0091] The method of Example 1 is different in that in step (1), zinc chloride is replaced by zinc nitrate, and finally the metal-modified adsorbent MA-11 is prepared.
[0092] The number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent MA-11 was 1.1×10 6 Pieces / mm 2 .
[0093] Example 12
[0094] The method of Example 1 is different in that in step (1), 1-butyl-3-methylimidazolium chloride ionic liquid is replaced by N-ethylpyridinium chloride ionic liquid, and finally metal-modified adsorbent MA-12 is prepared.
[0095] The number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent MA-12 was 1.3×10 6 Pieces / mm 2 .
[0096] Example 13
[0097] The method of Example 1 is different in that in step (2), ammonium cerium nitrate is replaced by potassium permanganate, and finally the metal-modified adsorbent MA-13 is prepared.
[0098] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-13 was 1.05×10 6 Pieces / mm 2 .
[0099] Embodiment 14
[0100] The method of Example 1 is different in that in step (3), the coconut shell activated carbon is replaced with activated alumina, and finally the metal-modified adsorbent MA-14 is prepared.
[0101] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-14 was 1.5×10 6 Pieces / mm 2 .
[0102] Embodiment 15
[0103] The method of Example 1 is different from that in step (4), the heating rate of the first drying treatment is replaced by 3°C / min from 0.5°C / min, and finally the metal-modified adsorbent MA-15 is obtained.
[0104] The number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent MA-15 was 1.7×10 6 Pieces / mm 2 .
[0105] Example 16
[0106] The method of Example 1 is different from that in step (4), the temperature of the second drying treatment is replaced by 180° C. from 150° C., and finally the metal-modified adsorbent MA-16 is obtained.
[0107] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent MA-16 was 1.6×10 6 Pieces / mm 2 .
[0108] Comparative Example 1
[0109] The method of Example 1 is different from that in step (1), zinc chloride is not used, and the metal-modified adsorbent SA-1 is finally prepared.
[0110] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent SA-1 was 2.5×10 6 Pieces / mm 2 .
[0111] Comparative Example 2
[0112] The method of Example 1 is different from that in step (1), glycerol is not used, and the metal-modified adsorbent SA-2 is finally prepared.
[0113] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent SA-2 was 3.2×10 6 Pieces / mm 2 .
[0114] Comparative Example 3
[0115] According to the method of Example 1, the difference is that in step (1), 1-butyl-3-methylimidazolium chloride ionic liquid is not used, and the metal modified adsorbent SA-3 is finally prepared.
[0116] like Figure 2 As shown in Figure 2, the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent SA-3 was 9.6×10 6 Pieces / mm 2 ; And in the obtained metal-modified adsorbent, the distribution of metal component particles shows that the content of metal agglomerates with a particle size of more than 30nm accounts for about 98wt%.
[0117] Comparative Example 4
[0118] The method of Example 1 is different in that step (2) is not performed, but the first metal salt solution is directly used in the equal volume impregnation process in step (3), and finally the metal modified adsorbent SA-4 is prepared.
[0119] The number of metal aggregates with a size of more than 20 nm on the metal-modified adsorbent SA-4 was 8.3×10 6 Pieces / mm 2 .
[0120] Comparative Example 5
[0121] Coconut shell activated carbon was directly used as adsorbent.
[0122] Test Case
[0123] The adsorbents obtained in Examples 1-16 and Comparative Examples 1-5 were subjected to adsorption experiments respectively. The specific process of the adsorption experiments is as follows: a certain amount of adsorbent is loaded, and the air tightness of the device is checked. After the air tightness of the device is checked to be good, the adsorption column is heated to 120°C, and nitrogen is continuously introduced for 2 hours to remove moisture and other gas impurities in the adsorbent, and then the temperature is naturally cooled to room temperature, and then the mixed gas is introduced for adsorption experiments. The PH3 concentration at the tail gas end is detected every 30 minutes using ammonium molybdate spectrophotometry. Among them, the mixed gas is a PH3 / H2 mixed gas, the concentration of PH3 is 100ppm (molar fraction), the volume space velocity of the mixed gas is 300mL (gas) / min·mL (adsorbent), and the adsorption experiment temperature is controlled at 30°C.
[0124] The data from the adsorption experiment at 2h were compared. The adsorption rates of the adsorbents obtained in Examples 1-16 and Comparative Examples 1-5 for PH3 impurities in the mixed gas are shown in Table 1. Each group of data was tested three times in parallel and the average value was taken. The calculation formula for the PH3 adsorption removal rate is: PH3 impurity adsorption rate (%) = [(initial content of PH3 impurities in the mixed gas before adsorption - content of PH3 impurities in the mixed gas after adsorption) / (initial content of PH3 impurities in the mixed gas before adsorption)] * 100%.
[0125] Table 1
[0126]
[0127]
[0128] From the data in Table 1, it can be seen that the PH3 impurity adsorption rates of Examples 1-16 using the technical solution of the present invention are all higher than those of Comparative Examples 1-5, and the PH3 impurity adsorption rates of some preferred embodiments can be as high as 98% or more. It can be seen that the metal-modified adsorbent prepared using the technical solution of the present invention has extremely high adsorption activity and stability for phosphine.
[0129] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A metal-modified adsorbent, characterized in that: The metal-modified adsorbent comprises an adsorption carrier and a copper-containing active component, an auxiliary metal component and an oxidation auxiliary component loaded on the adsorption carrier, wherein the adsorption carrier is also loaded with an ionic liquid; the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 the following.
2. The metal-modified adsorbent according to claim 1, wherein: The number of metal agglomerates with a size of more than 20 nm on the metal modified adsorbent is 2×10 6 Pieces / mm 2 Below, preferably 1.5×10 6 Pieces / mm 2 Below, more preferably 1.2×10 6 Pieces / mm 2 Below, more preferably 0.2×10 6 -0.8×10 6 Pieces / mm 2 .
3. The metal-modified adsorbent according to claim 1 or 2, wherein: The loading amount of copper element in the metal modified adsorbent is 1-15 wt %, preferably 5-10 wt %.
4. The metal-modified adsorbent according to any one of claims 1 to 3, wherein: The molar ratio of the copper-containing active component to the molar ratio of the auxiliary metal component is 1:0.01-2, preferably 1:0.05-1; Preferably, the ratio of the total molar amount of the copper-containing active component and the auxiliary metal component, the molar amount of the oxidation auxiliary component and the molar amount of the ionic liquid is 1:0.05-0.5:0.1-2, preferably 1:0.1-0.3:0.3-1.
5.
5. The metal-modified adsorbent according to any one of claims 1 to 4, wherein: The adsorption carrier is selected from one or more of activated carbon, molecular sieve, activated alumina, silica gel, titanium dioxide and ceramics, preferably one or more of coconut shell activated carbon, fruit shell activated carbon, wood activated carbon, coal activated carbon, resin-based activated carbon and rubber activated carbon, more preferably one or more of coconut shell activated carbon, fruit shell activated carbon and wood activated carbon; And / or, the copper-containing active component is selected from one or more of copper halides, sulfates, nitrates and acetates, preferably one or more of copper halides, more preferably one or more of copper chlorides, and further preferably cupric chloride and / or cuprous chloride; and / or, the auxiliary metal component is selected from one or more of halides, sulfates, nitrates and acetates of iron, silver, zinc, cerium, cobalt and nickel, preferably one or more of halides of iron, silver, zinc, cerium, cobalt and nickel, more preferably one or more of chlorides of iron, silver, zinc, cerium, cobalt and nickel, further preferably one or more of ferric chloride, silver chloride, zinc chloride, cerium chloride, cobalt chloride and nickel chloride; And / or, the oxidation aid component is selected from one or more of cerium salts, molybdenum salts and manganese salts, preferably one or more of cerium salts, more preferably ammonium cerium nitrate and / or cerium sulfate; And / or, the cation in the ionic liquid is selected from one or more of imidazolium cations, pyridinium cations, quaternary ammonium salt cations, quaternary phosphonium salt cations and morpholine cations, and the anion is selected from BF4 - PF6 - 、F - , Cl - Br - and I - More preferably, the cation in the ionic liquid is selected from one or more of imidazole cations and quaternary ammonium salt cations, and the anion is selected from Cl - Br - and I - One or more of .
6. A method for preparing the metal-modified adsorbent according to any one of claims 1 to 5, the method comprising the following steps: (1) preparing a first metal salt solution including a copper-containing active component, an auxiliary metal component, a dispersant and an ionic liquid; (2) adding an oxidizing agent component to the first metal salt solution to obtain a second metal salt solution; (3) contacting the second metal salt solution with an adsorption carrier so that the copper-containing active component, the auxiliary metal component, the oxidation auxiliary component and the ionic liquid are loaded on the adsorption carrier to obtain a metal-modified precursor; (4) drying the metal-modified precursor to obtain the metal-modified adsorbent; The method enables the obtained metal-modified adsorbent to satisfy the following conditions: the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2.3×10 6 Pieces / mm 2 the following.
7. The method according to claim 6, wherein: The method enables the obtained metal-modified adsorbent to satisfy the following conditions: the number of metal agglomerates with a size of more than 20 nm on the metal-modified adsorbent is 2×10 6 Pieces / mm 2 Below, preferably 1.5×10 6 Pieces / mm 2 Below, more preferably 1.2×10 6 Pieces / mm 2 Below, more preferably 0.2×10 6 -0.8×10 6 Pieces / mm 2 .
8. The method according to claim 6 or 7, wherein: The dispersant is selected from one or more of ethylene glycol, glycerol, tannic acid, polyethylene glycol, polyacrylamide and polyvinyl pyrrolidone, preferably one or more of ethylene glycol, glycerol and polyvinyl pyrrolidone; and / or, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component, the amount of the dispersant is 0.001-0.1 mol, preferably 0.005-0.05 mol; and / or, the solvent of the first metal salt solution is selected from one or more of water, methanol, ethanol, propylene glycol, acetonitrile, acetone, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone, preferably one or more of water, methanol, ethanol, acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone; and / or, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component, the amount of the solvent of the first metal salt solution is 15-500 mL, preferably 35-350 mL; and / or, relative to 1 mol of the copper-containing active component, the amount of the auxiliary metal component is 0.01-2 mol, preferably 0.05-1 mol; And / or, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component, the amount of the ionic liquid used is 0.1-2 mol, preferably 0.3-1.5 mol.
9. The method according to any one of claims 6 to 8, wherein: The oxidation aid component is provided in the form of a solution, and the solvent for dissolving the oxidation aid component is selected from one or more of water, methanol, ethanol, propylene glycol, acetonitrile, acetone, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone, preferably one or more of water, methanol, ethanol, acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and 1,3-dimethylimidazolidinone; Preferably, relative to 1 mol of the oxidation aid component, the amount of the solvent for dissolving the oxidation aid component is 15-500 mL, preferably 35-350 mL; Preferably, when the oxidation aid component is provided in the form of a solution, the solution is acidic; more preferably, the pH of the solution of the oxidation aid component is 5.5-6.5; Preferably, the amount of the oxidation auxiliary component is 0.05-0.5 mol, preferably 0.1-0.3 mol, relative to 1 mol of the total amount of the copper-containing active component and the auxiliary metal component.
10. The method according to any one of claims 6 to 9, wherein: The drying process includes subjecting the metal-modified precursor to a first drying process and a second drying process; Preferably, the conditions of the first drying treatment include: temperature 60-90°C, time 2-36h, heating rate 0.1-3°C / min; preferably temperature 70-80°C, time 6-12h, heating rate 0.5-2°C / min; Preferably, the conditions of the second drying treatment include: temperature 100-180°C, time 4-16h, heating rate 4-8°C / min; preferably temperature 120-160°C, time 6-12h, heating rate 5-7°C / min.
11. Use of the metal-modified adsorbent according to any one of claims 1 to 5 in the purification of circulating hydrogen.
Citation Information
Patent Citations
Recycling hydrogen purification processing method for producing polysilicon by reducing trichlorosilane
CN102328906B
A method and device for repurifying circulating hydrogen
CN105293438B
Method for purifying hydrogen for electronic grade polycrystalline silicon production
CN113233420A
Method for purifying circulating hydrogen in polycrystalline silicon production
CN117263141A
Cited By
Polycrystalline silicon adsorbent as well as preparation method and regeneration method thereof
CN122499761A
Polysilicon adsorbent and methods of making and regenerating the same
CN122499761B